Determinants of stunting in urban and rural areas of Indonesia: A systematic review - Tjokorda Istri Anom Fanny Dewi; Nia Novita Wirawan; Nurul Muslihah (AcTion: Aceh Nutrition Journal, 2025)
Stunting, a chronic form of undernutrition, is linked to impaired growth, delayed cognitive development, and adverse health and economic outcomes across the life course. Environmental, socioeconomic, and behavioral variations between urban and rural settings contribute differently to stunting risk, although the evidence remains fragmented. This study systematically reviewed the determinants of stunting in urban and rural Indonesia to provide a comprehensive and contextual understanding. The review followed the PRISMA guidelines, with searches conducted in PubMed, Scopus, and Web of Science restricted to the past ten years. The methodological quality of the eligible studies was appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. From 659 initial records, 11 studies met the inclusion criteria: 4 focused on urban settings, 4 on rural settings, and 3 covered both. The prevalence of stunting in rural areas of Indonesia reached 53,3%, compared to 34,9% in urban areas. Rural stunting is primarily associated with structural and service-related limitations, including inadequate health services, sanitation, and maternal education. In contrast, urban stunting was more strongly associated with behavioral factors, particularly unhealthy dietary practices such as excessive snack consumption. These findings highlight the need for context-specific interventions, prioritizing structural improvements in rural areas and promoting healthier dietary behaviors in urban areas.